Lipid bilayer composition as a determinant of cancer cell sensitivity to tumoricidal protein‐lipid complexes. (7th April 2022) - Ho, James C. S.; Mir, Sartaj Ahmad; Cavalera, Michele; Esmaeili, Parisa; Tran, Tuan Hiep; Yann, Zandra Chew; Tran, Thi Hien; Chaudhuri, Arunima; Bendt, Anne K.; Wenk, Markus R.; Svanborg, Catharina
Abstract: Complexes formed by the alpha1 N‐terminal peptide of alpha‐lactalbumin and oleic acid (alpha1‐oleate) interact with lipid bilayers. Plasma membrane perturbations trigger tumor cell death but normal differentiated cells are more resistant, and their plasma membranes are less strongly affected. This study examined membrane lipid composition as a determinant of tumor cell reactivity. Bladder cancer tissue showed a higher abundance of unsaturated lipids enriched in phosphatidylcholine, PC (36:4) and PC (38:4), and sphingomyelin, SM (36:1) than healthy bladder tissue, where saturated lipids predominated and the lipid extracts from bladder cancer tissue inhibited the tumoricidal effect of the complex more effectively than healthy tissue extracts. Furthermore, unsaturated PC in solution inhibited tumor cell death, and the complex interacted with giant unilamellar vesicles formed by PC, confirming the affinity of alpha1‐oleate for fluid membranes enriched in PC. Quartz Crystal Microbalance with dissipation monitoring (QCM‐D) detected a preference of the complex for the liquid‐disordered phase, suggesting that the insertion into PC‐based membranes and the resulting membrane perturbations are influenced by membrane lipid saturation. The results suggest that the membrane lipid composition is functionally important and that specific unsaturated membrane lipids may serve as "recognition motifs" for broad‐spectrum tumoricidal molecules such as alpha1‐oleate.